Did The Economic Indicators Influence the Formation of Business Confidence In Poland During The COVID-19 Pandemic? - Marcin OLKIEWICZ (Communications of International Proceedings, 2022)
The aim of the publication is an attempt to show whether changes in economic indicators affect business confidence in Poland during the COVOD-19 pandemic. Business confidence for entrepreneurs is important because it is significantly related to the development of entrepreneurship and determines the decision-making process. It is also supposed to ensure the stable development and functioning of the organization, which will be shown by the results of the research. The analysis of the collected data covering the years 2015-2021 showed that this study should be treated as a survey study, which gives the opportunity to deepen the area and scope of the research. The study assessed Poland and, in some cases, the G7 countries for comparative purposes. The presented research results indicate that there is a relationship between the COVID-19 pandemic and economic indicators. There is also such a relationship between the business confidence index (BCI). This is particularly evident in the period of the COVID-19 pandemic development at the turn of Q1 and Q2 2020. During this period, the indicator takes negative values. This study also showed that in the initial period of the COVID-19 pandemic, the increasing incidence rate increased the feeling of uncertainty in running and developing business, as indicated by the calculated Pearson correlation coefficient -0.3982.
Keywords: business confidence index (BCI); COVID-19; gross domestic product (GDP); unemployment.